Ku prawdziwej rozkoszy. O możliwym wzorcu utrakwistycznego modelu wychowania kobiet - Łazarz, Radosław (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The Reformation introduced new concepts of education, compared to the medieval axiological model of lives of the saints and became the Scripture. The main role of the Bible became evident also in environments inspired by the Reformation thought. Among them was the community of Utraquists in the Bohemia kingdom. This church is derived directly from the tradition of the Hussite and have their own ethical standards. In religiously divided the Bohemia of early modern of its specificity decided, among others, a wide range of social and significant share of the middle class. Egalitarian nature of utraquism favored the popularity the concept of education and learning, especially on good Christian life. One of them is the treaty Adam Clement Plznensky addressed to virgins. The Treaty applies to a proper understanding of pleasure and the means by which it can be achieved or enhanced. The author identifies a real pleasure with the feelings of the heart and the soul. The pattern of education of utraquists young ladiesis based largely on the knowledge of Scripture, whether it comes from listening to or reading from their own, diligence, modesty and avoiding temptations that threaten the soul. Thanks to this „Wise Virgins” can count on the good life with Christ, both temporal and after death. The opposite of this educational model is „Foolish Virgins” attached to the pleasures of the body, which therefore can not achieve real pleasure.
Keywords: Adam Clement Plznensky; education; moral education; parenetic literature; Utraquism